Диверсифікація товаропотоків підприємств в зовнішньоекономічній діяльності - Коваленко, Катерина Сергіївна (Національний університет "Львівська політехніка", 2017)
Дисертацію присвячено розкриттю теоретико-методологічних основ та розробці практичних рекомендацій щодо диверсифікації товаропотоків. Узагальнено основні властивості, види та характеристики товаропотоків. Окреслені основні підходи до трактування диверсифікації. Розкрито сутність поняття диверсифікації товаропотоків. Проаналізовано діяльність вітчизняних підприємств з виробництва харчових продуктів, визначені основні тенденції розвитку міжнародних вхідних та вихідних харчових товаропотоків та виявлено збалансованість бізнес-портфелів вітчизняних диверсифікованих компаній. Доведено ефективність впровадження стратегії диверсифікації товаропотоків в оптимальний момент на основі моделі TRTC. Удосконалено метод оцінювання ефективності диверсифікації товаропотоків шляхом обрахунку не тільки фінансових, але ще і нефінансових результатів. Диссертация посвящена раскрытию теоретико-методологических основ и разработке практических рекомендаций по диверсификации товаропотоков. Обобщены основные свойства, виды и характеристики товаропотоков. Очерчены основные подходы к трактовке диверсификации. Раскрыта суть понятия диверсификации товаропотоков. Проанализирована деятельность отечественных предприятий по производству пищевых продуктов, определены основные тенденции развития международных входных и выходных пищевых товаропоротоков и выявлена сбалансированность бизнес-портфелей отечественных диверсифицированных компаний. Доказана эффективность внедрения стратегии диверсификации товаропотоков в оптимальный момент на основе модели TRTC. Усовершенствован метод оценки эффективности диверсификации товаропотоков путем расчета не только финансовых, но еще и нефинансовых результатов. The purpose of the dissertation research is theoretical substantiation and development of methodical and applied recommendations for diversification of goods flows of enterprises in foreign economic activity. Object of the research is the process of diversification of goods flows of enterprises in foreign economic activity. The subject of the study are theoretical and methodological and applied provisions for the substantiation and assessment of the diversification of goods flows of enterprises in foreign economic activities. In the first section "Theoretical basis of diversification of goods flows of enterprises in foreign economic activity", the essence, types, motives and risks of diversification of commodity flows in foreign economic activity were clarified. Particular attention is paid to studying the category of "commodity flows" of its classification and characteristics. The results of the review and synthesis of literary sources have shown that the term "commodity flow" is often identified with similar content categories: "material flow", "economic flow" and "commodity turnover". However, commodity flows are only a part of all these components. In view of this, it is expedient to understand the movement of a certain quantity and assortment of goods from the manufacturer to the end user for a certain period of time, with the corresponding transport, using all the distribution units in the course of which logistic operations are performed on them. It is proposed to classify the trade flows on the basis of two properties - the type of product and the specificity of the flow. Trade flows of enterprises engaged in foreign economic activity inherent in a number of specific characteristics that occur due to changes in the jurisdiction of the owner, so all the characteristics of trade flows is advisable classified into general and specific characteristics. Specific trade flows in foreign trade stipulated the presence of certain restrictions that accompany import-export operations and specifies the customs procedures, which alter the characteristics of goods traffic, increase its value through the imposition of Volume and reduce speed due to the additional time spent on paperwork certifying the quality, origin, manufacturer, product and so on. Diversification as an economic category has a wide range of applications and is used to interpret various economic processes. A thorough study of the views of scholars has revealed three approaches to the interpretation of diversification: 1) as a type of corporate strategy; 2) as a marketing strategy; 3) as a method of reducing investment risks. To investigate the flow of goods, it is expedient to treat diversification as a strategy that provides the company with a way out of the main business, penetration into new types of activities and spheres of management, expansion of the assortment of goods groups in order to avoid fluctuations of the profits and reduce the risk. Based on the analysis of common and distinctive features of existing methods for assessing the effectiveness of diversification, four groups have been formed. The methods of each group have their advantages and disadvantages: most of the proposed methods do not fully assess the effectiveness of diversification of merchandise flows alone, and the correct results are only those whose calculation is based on several simultaneously involved methods. On the basis of this, a method for assessing the diversification of commodity flows through the calculation of financial results for non-financial results, which the enterprise receives through the diversification of trade flows, is formed. The second section of the dissertation research "Analysis of commodity flows of enterprises for the production of food products" is devoted to the study of the peculiarities of the formation of food commodity flows. The analysis of the internal market of food commodity flows, the tendencies of the development of the foreign food production market and the formation of the commodity structure of the diversification of foreign economic activity of enterprises based on the matrix ADL/LC. Analysis of the state of diversification of trade flows of domestic food production enterprises has determined that most of the analyzed enterprises carry out marketing diversification, by implementing similar projects in order to increase consumers. But, despite the goal of diversification, according to a study, the effectiveness of diversification depends on the success of the project, and in some enterprises it is not. Based on the ADL / LC model, it has been found that the business portfolios of the analyzed food companies are unbalanced, that is, business projects of the enterprises do not allow to predict that the period of profitability of such enterprises will be long. In the third section "Improvement of organizational and methodical principles for the diversification of foreign economic activity of enterprises", measures for increasing the efficiency of the strategy of diversification of commodity flows at food-processing enterprises were substantiated; Methods of assessing the effectiveness of diversification of commodity flows have been improved and a mechanism for increasing the quality of diversification of commodity flows has been developed. On the basis of mathematical and graphic models it is proved that by introducing diversification of trade flows, the enterprise increases the period of its profitability. Based on the TRTC model and comparisons of marginal revenue and expenditure, it has been formed that the use of diversification in the optimal period of the enterprise increases its profitability, which makes it possible to assert that the use of such a strategy at the enterprise yields results in the form of increase in yield. A method of managing diversification has been developed. Method of managing the diversification of commodity flows in foreign economic activity is developed, depending on the element of expansion, which consists of two aspects - as a process of realization of the set goals of the enterprise through projects, and as an optimization of the logistic process of the enterprise. The method of managing diversification of goods flows through projects is appropriate when the company has clearly defined goals and objectives, and the process of their implementation is realistic for the enterprise. The method of managing diversification in the logistics system involves changes in the supply chain due to the expansion of the directions of incoming and outgoing goods at the enterprise.
Диверсификация товаропотоков предприятий во внешнеэкономической деятельности
Diversification of goods flows of enterprises in foreign trade activities
Keywords: диверсифікація; товаропотоки; зовнішньоекономічна діяльність; виробництво харчових продуктів; ефективність; проект; оптимальний момент; диверсификация; товаропотоки; внешнеэкономическая деятельность; производство пищевых продуктов; эффективность; проект; оптимальный момент; diversification; commodity flows; foreign economic activity; production of food products; efficiency; project; optimal moment